Molecular Docking Insights of Newly Synthesized Schiff Base Monomers and Evaluating the Anticancer Activity of Their Polymers - Ibrahim, A. Mohammed; Shabeer, T.K. (Annals of the National Academy of Medical Sciences (India), 2023)
Introduction The molecular docking technique has shown efficacy with small molecules but faces challenges when applied to macromolecules. To overcome this limitation, a focused approach targeting the active repeat units (monomers) of macromolecules was adopted. This study synthesized ten new dihydroxy Schiff base monomers (SBM1-SBM10) featuring azo moieties and alkoxy side groups. These were attached to human 3-alpha-hydroxysteroid dehydrogenase type 3 (4XO6), a protein linked to breast cancer, using molecular docking via the AutoDock tool.Materials and Methods The synthesis of dihydroxy Schiff base monomers SBM1-SBM10 with azo moieties and alkoxy side groups was carried out. These synthesized monomers were then docked with human 3-alpha-hydroxysteroid dehydrogenase type 3 (4XO6) utilizing AutoDock. Among these, the most promisingly docked monomer, SBM8, was selected for further experimentation. SBM8 was polymerized with terephthaloyl chloride to produce a novel polyester termed PolySyringaldehydeDiaminodiphenylSulfone (PSDS). The anticancer activity of PSDS was assessed using the MCF7 human breast cancer cell line. Concurrently, its cytotoxicity was evaluated via the MTT assay employing a normal VERO cell line.Results The molecular docking analysis revealed the best-docked monomer, SBM8, which was subsequently used for the synthesis of PSDS. The newly formed polyester, PSDS, demonstrated significant anticancer properties against the MCF7 human breast cancer cell line. Simultaneously, the cytotoxicity evaluation on the normal VERO cell line indicated a favorable safety profile for PSDS.Conclusion The study's findings highlight the successful synthesis and docking of dihydroxy Schiff base monomers with 4XO6, resulting in the creation of PSDS. This newly synthesized polyester, PSDS, exhibited promising anticancer activity against the MCF7 cell line while demonstrating minimal cytotoxicity towards normal VERO cells. These results suggest the potential of PSDS as a targeted therapeutic agent against breast cancer, warranting further investigation and development.
Keywords: docking; monomers; anticancer activity; polymers; breast cancer